Cost effectiveness and budget impact of universal varicella vaccination in Russia - Alen Marijam; Ekaterina Safonova; Mikhail Scherbakov; Evgeniy Shpeer; Desirée Van Oorschot; Alla Rudakova; Vladimir Tatochenko; Nikolay Briko (Taylor & Francis Group, 2022)
This economic evaluation assesses the cost-effectiveness and budget impact of introducing a two-dose varicella vaccine in the Russian national immunization program. A static Markov model followed a simulated 2019 Russian cohort over its lifetime and compared outcomes and costs of three varicella vaccination strategies: strategy I (doses given at 12 and 15 months of age), strategy II (doses given at 1 year and 6 years of age), and a no vaccination scenario. Inputs on age-dependent clinical pathways, associated costs, and related health outcomes were collected from national sources and published literature. Results are presented as incremental cost-effectiveness ratio (ICER) from the healthcare payer and societal perspective over the lifetime of the birth cohort and the budget impact over a 10 years' time horizon. Vaccination strategies I and II resulted in an ICER of approximately 1.7 million rubles per quality-adjusted life years gained from the healthcare payer perspective and were cost-saving from the societal perspective. From the healthcare payer perspective, the costs per varicella case averted were 5,989 and 7,140 rubles per case for strategies I and II, respectively. However, from the societal perspective, vaccination is a dominant strategy and the budget impact analysis shows significant healthcare savings over 10 years, with strategy I realizing savings of ~2 billion rubles more than strategy II. From a public health impact perspective, varicella vaccination of children at 12 and 15 months of age through the Russian NIP is expected to be cost-effective with an affordable budget impact compared to no vaccination.